2021
DOI: 10.1186/s12940-021-00783-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of acrylamide with non-alcoholic fatty liver disease in American adults: a nationwide cross-sectional study

Abstract: Background Acrylamide (AA) is a toxicant to humans, but the association between AA exposure and the risk of non-alcoholic fatty liver disease (NAFLD) remains unclear. In this study, our objective is to examine the cross-sectional association between AA exposure and the risk of NAFLD in American adults. Methods A total of 3234 individuals who took part in the National Health and Nutrition Examination Survey (NHANES) 2003–2006 and 2013–2016 were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Previous studies revealed that serum and hepatic advanced glycation end-products were significantly elevated in non-alcoholic steatohepatitis patients (44) , and the circulating level of advanced glycation end-products was associated with IR even in non-obese, non-diabetic subjects (45) . In addition, acrylamide (one of the Maillard reaction products) was also associated with NAFLD in the NHANES (46) . Another interpretation concerns the wide range of food additives in UPF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that serum and hepatic advanced glycation end-products were significantly elevated in non-alcoholic steatohepatitis patients (44) , and the circulating level of advanced glycation end-products was associated with IR even in non-obese, non-diabetic subjects (45) . In addition, acrylamide (one of the Maillard reaction products) was also associated with NAFLD in the NHANES (46) . Another interpretation concerns the wide range of food additives in UPF.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, results of subsequent surveys have continued to demonstrate that Hb adducts of GA are measurable in the US population. For example, Liu et al (2021) reported Hb-GA/Hb-AA ratios in the region of 0.7-1.1 in 3,234 participants of the 2003-2006 and 2013-2016 surveys. Similarly, in Europe, Hb adducts of both AA and GA have been measured in the European Prospective Investigation into Cancer and Nutrition (EPIC). For example, median Hb-GA/Hb-AA ratios of 0.7-1.0 were reported in a subgroup of 801 non-smoking postmenopausal women from 8 European countries (Obon-Santacana et al, 2017).…”
Section: Measurement Of Haemoglobin Adductsmentioning
confidence: 99%
“…9,10 Epidemiological evidence revealed that the ratio of HbGA to HbAA (HbGA/HbAA) was positively associated with triglyceride, obesity, and nonalcoholic fatty liver disease in American adults. 10,23,24 Previous studies reported that HbAA was inversely associated with the serum insulin. 25 Similarly, a recent study from NHANES found an inverse relationship between HbAA and diabetes prevalence and demonstrated a higher prevalence of diabetes mellitus in relation to the HbGA/HbAA ratio.…”
Section: ■ Introductionmentioning
confidence: 99%
“…AA can directly be conjugated with glutathione and subsequently be epoxidated into glycidamide (GA) via the cytochrome P450 2E1 in vivo . AA and its primary metabolite GA could link with hemoglobin to generate the adduct of AA (HbAA) and adduct of GA (HbGA), which are used as long-term biomarkers of AA exposure. , Meanwhile, the ratio of HbGA to HbAA (HbGA/HbAA) considered as a potential biomarker of metabolic capacity of AA and the sum of HbAA and HbGA (HbAA + HbGA) were found to have complex links to diabetes and obesity. , Epidemiological evidence revealed that the ratio of HbGA to HbAA (HbGA/HbAA) was positively associated with triglyceride, obesity, and non-alcoholic fatty liver disease in American adults. ,, Previous studies reported that HbAA was inversely associated with the serum insulin . Similarly, a recent study from NHANES found an inverse relationship between HbAA and diabetes prevalence and demonstrated a higher prevalence of diabetes mellitus in relation to the HbGA/HbAA ratio .…”
Section: Introductionmentioning
confidence: 99%